2022
DOI: 10.14746/quageo-2022-0038
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of urban garden initiatives for food security in Kuala Lumpur, Malaysia

Abstract: Sustainable urban farming is a strategy to improve food availability and food access, and to support food security for the urban population in Malaysia. However, the development of these activities has been affected by several constraints. This article aims to identify the challenges faced by urban farmers in Kuala Lumpur. The challenges of practicing urban gardening were categorised into five groups (technical, resource-related, economic, social and environmental factors). Data were collected via a questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
1
2
0
1
Order By: Relevance
“…1 ). The lower percentage of female farmers, which is consistent with previous reports [ [50] , [51] , [52] , [53] ], could be due to a lack of opportunities to participate in cooperative organisations, and policies that tend to overlook them [ 54 ]. The lack of opportunities among females may also contribute to the differences in knowledge on agroecology between males and females ( Table 1 ).…”
Section: Discussionsupporting
confidence: 88%
“…1 ). The lower percentage of female farmers, which is consistent with previous reports [ [50] , [51] , [52] , [53] ], could be due to a lack of opportunities to participate in cooperative organisations, and policies that tend to overlook them [ 54 ]. The lack of opportunities among females may also contribute to the differences in knowledge on agroecology between males and females ( Table 1 ).…”
Section: Discussionsupporting
confidence: 88%
“…The vegetables were grown in a confined space that provided a conducive environment for plant growth. HAVVA Agrotech Sdn Bhd is another company based in Penang that fully utilised and optimised space to grow vegetables two times faster [14]. HAVVA Agrotech, shown in Figure 3, integrated hydroponic, aquaculture, vertical farming, fermionic and aeroponic into a single, effective and efficient urban farming technology.…”
Section: Urban Farmingmentioning
confidence: 99%
“…3. HAVVA Agrotech [14] Research has also shown that, despite its popularity, farmers still face challenges in urban framing, such as weather conditions, land availability, and financial issues [15,16]. Certain urban areas are vulnerable to weather changes.…”
Section: Fig 2 Cityfarm Malaysia [13]mentioning
confidence: 99%
“…Periodā no 2013.-2019.gadam, kas ir CSP publicētais periods par valstspilsētām, Rīga vidēji veido 54.14% Zemes resursu cenas ir viens no faktoriem ar vislielāko negatīvo ietekmi urbānās lauksaimniecības attīstībai. Tas ir izaicinājums globālās prakses pieredzē, un tiek izmantots kā ietekmējošais faktors arī citos urbānās lauksaimniecības pētījumos(Asl, Azadgar, 2022;Ishak et al, 2022). Pēc VZD kadastrālo vērtību bāzes datiem (Kadastrālo vērtību bāze, 2020) pilsētas teritoriju zemei, uz kuras galvenā saimnieciskā darbība ir lauksaimniecība, augstākā vērtība ir Rīgā (1 EUR m -2 ), salīdzinoši zemāka pārējās valstspilsētās, bet novados vidējā vērtība ir 0.09 EUR m -2 , ar modu 0.07 EUR m -2 (skat.…”
unclassified